Determination of velocity, pressure and heat transfer of a steady state flow of third order fluid using homotopy analysis method - A.Mahdi, Walaa; Abdullatif, Sabah (Journal of Madenat Alelem University College, 2023)
This paper, focused on a steady flow of non-Newtonian fluid of three order in a porous walls vertical channel. The equations were used to describe it’s state of motion and the energy equations. The velocity, pressure variations and heat transfer profiles investigated by using Homotopy Analysis Method and examining qualitatively the effect of non-Newtonian parameters (α, β, ) which are dimensionless numbers, Reynolds number (Re), Hartmann number (M), and Peclet number (Pe) on these values. Finally varies numerical simulations were taken to enhance the analytical results.